BANK FUNDS MANAGEMENT AND ITS EFFECTS ON NET INTEREST MARGIN - Hesti Budiwati (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2020)
The purpose of this study is to study the effect of bank fund management on Net Interest Margin. Bank fund management in this study uses the Interest Expense Ratio, the Interest Rate Risk Ratio and the Loan to Deposit Ratio. The study was conducted at BPR in Indonesia. The sample taken was 65 banks using quarterly financial statements for 4 quarterly periods for each bank. With a purposive sampling technique, a sample of 260 BPR financial reports was obtained. The method used is multiple linear regression analysis. The results of the study stated that the Interest Cost Ratio, Interest Risk Ratio and Loan to Deposit Ratio have a significant effect both partially and simultaneously on the Net Interest Margin with a positive relationship direction. Overall, 15.7% of the net interest margin at BPR in Indonesia can be discussed by the Interest Cost Ratio, Interest Rate Risk Ratio and Loan to Deposit Ratio. While the remaining 84.3% of the net interest margin is determined by other variables. Future studies are expected to examine other variables that use bank profits.